Cellulose based polymers in development of amorphous solid dispersions - Rahul B Chavan; Sneha Rathi; Vaskuri G S Sainaga Jyothi; Nalini R Shastri (Elsevier, 2019)
Cellulose derivatives have gained immense popularity as stabilizers for amorphous solid dispersion owing to their diverse physicochemical properties. More than 20 amorphous solid dispersion-based products that have been approved for marketing consist of cellulose derivatives as stabilizers, thus highlighting their importance in generation of amorphous solid dispersions. These polymers offer numerous advantages like drug solubilization, crystallization inhibition and improvement in release patterns of drugs. Exploring their potential and exploiting their chemistry and pH responsive behaviour have led to the synthesis of new derivatives that has broadened the scope of the use of cellulose derivatives in amorphous formulation development. The present review aims to provide an overview of different mechanisms by which these cellulose derivatives inhibit the crystallization of drugs in the solid state and from supersaturated solution. A summary of different categories of cellulose derivatives along with the newly explored polymers has been provided. A special segment on strengths, weaknesses, opportunities, and threats (SWOT) analysis and critical quality attributes (CQAs) which affect the performance of the cellulose based amorphous solid dispersion will aid the researchers in identifying the major challenges in the development of cellulose based solid dispersion and serve as a guide for further formulation development. Keywords: Supersaturation, HPMC, Amorphous form, Crystallization, Polymers